Continuous male presence required for fertilization in captive painted dragons, Ctenophorus pictus. - Uller, T; Olsson, M (2005)
Understanding proximate determinants of reproductive events is an important issue for many biologists. In the present paper, we show that follicular recruitment and fertilization are dependent on male stimuli in long-term captive female painted dragon lizards, Ctenophorus pictus. Hibernated females kept separated from males did not initiate reproduction, despite visual contact with displaying males and repeated copulation attempts. Follicular stimulating hormone stimulated ovarian growth and female receptivity, but did not result in successful fertilization of eggs, despite repeated copulations. When housed continuously together with males, however, follicle recruitment and fertilization were achieved. Thus, not only ovarian growth, but also fertilization, is dependent on male stimuli.